2005
DOI: 10.1902/jop.2005.76.11.1849
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Crevicular Fluid Levels of Monocyte Chemoattractant Protein‐1 and Tumor Necrosis Factor‐Alpha in Patients With Chronic and Aggressive Periodontitis

Abstract: These results suggest that MCP-1 could have an important role in the activation and recruitment of inflammatory and immune cells in periodontal diseases, and both AgP and CP patients may have the same pattern of MCP-1 expression. A strong positive correlation between the GCF levels of MCP-1 and TNF-alpha may account for the mechanism of amplification of inflammatory events in gingival inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 31 publications
13
114
2
5
Order By: Relevance
“…This later hypothesis is supported by studies showing that periodontal subjects with specific polymorphisms in the IL-1 gene produce 2.5 more IL-1β in shallow pockets than subjects having periodontitis but without these polymorphisms [25]. IL-6, TNF-α, IL-17, IL-8 and MCP-1 have also been found to be increased in GCF of patients with PD [47,59].…”
Section: Local Host Response In Periodontitismentioning
confidence: 85%
“…This later hypothesis is supported by studies showing that periodontal subjects with specific polymorphisms in the IL-1 gene produce 2.5 more IL-1β in shallow pockets than subjects having periodontitis but without these polymorphisms [25]. IL-6, TNF-α, IL-17, IL-8 and MCP-1 have also been found to be increased in GCF of patients with PD [47,59].…”
Section: Local Host Response In Periodontitismentioning
confidence: 85%
“…There is considerable evidence that diabetes enhances the innate immune response in the periodontium. IL-1beta, TNF-alpha and the chemokine MCP-1 are elevated in the gingival crevicular fluid or serum of diabetic patients and are correlated with increased periodontal tissue destruction (69)(70)(71)(72). Monocytes from patients with type 1 diabetes produce significantly greater amounts of TNF-alpha, IL-1beta and PGE2 in response to LPS compared to matched normoglycemic individuals (72,73).…”
Section: Periodontal Diseasementioning
confidence: 99%
“…Therefore, it is believed that the intensity of periodontal inflammation could be assessed objectively by analyzing GCF components, because many inflammatory and immune mediators implicated in periodontal destruction have been detected in GCF. Several researchers have reported that the expression of inflammatory cytokines such as IL-1, IL-6, IL-8 and TNF-α in GCF from chronic periodontitis patients was significantly elevated when compared with healthy patients [22] [23] [24] [25]. Furthermore, there are some reports investigating the effect of nonsurgical periodontal therapy involving SRP on GCF from patients with chronic periodontitis [26] [27].…”
Section: Discussionmentioning
confidence: 99%